2023
DOI: 10.1039/d3fo01332d
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Seabuckthorn (Hippophae rhamnoides L.) restore CUMS-induced depressive disorder and regulate the gut microbiota in mice

Chen-Xi Xia,
Alex Xiong Gao,
Yue Zhu
et al.

Abstract: Seabuckthorn (Hippophae rhamnoides L.), having an enrichment of flavonoids including isorhamnetin, quercetin and kaempferol, is a representative example of “medicine food homology” targeting at several diseases. Major depressive disorders seriously...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Tyrosine and tryptophan are typical aromatic amino acids that are metabolized by Lachnospiraceae, which is one of the main microbial pathways in the human gut that produces indole-propionic acid, indole, phenol, and p-cresol [43]. In addition, Lachnospiraceae has been found to be signi cantly associated with attenuating in ammation in obese [44] and CUMS mice [45]. Consistent with previous research, uncultured_f_Lachnospiraceae and unclassi ed_f_Lachnospiraceae were drastically and poorly associated with pro-in ammatory cytokines.…”
Section: Discussionsupporting
confidence: 86%
“…Tyrosine and tryptophan are typical aromatic amino acids that are metabolized by Lachnospiraceae, which is one of the main microbial pathways in the human gut that produces indole-propionic acid, indole, phenol, and p-cresol [43]. In addition, Lachnospiraceae has been found to be signi cantly associated with attenuating in ammation in obese [44] and CUMS mice [45]. Consistent with previous research, uncultured_f_Lachnospiraceae and unclassi ed_f_Lachnospiraceae were drastically and poorly associated with pro-in ammatory cytokines.…”
Section: Discussionsupporting
confidence: 86%
“…As seen with kaempferol and quercetin alone, G. biloba potentiates PI3K/AKT relative to CREB signaling to promote neuroplasticity [287,[289][290][291][292][293]. Hippophae rhamnoides extracts are also rich in quercetin and kaempferol, and they enhanced neuronal differentiation and neurite outgrowth via PI3K/AKT and ERK signaling [294,295]. However, clinical trials have revealed the inconsistent efficacy of G. biloba on cognition and other AD-related parameters [296].…”
Section: Quercetin and Kaempferol In Common Herbsmentioning
confidence: 99%
“…Panax ginseng + + Neuroprotective [175,187,225,278,310] Morenga oleifera + + Memory improvement [300][301][302] Cuscuta chinensis + + Memory improving, Neuroprotective, Hepatoprotective, Immunomodulatory [311] Allium cepa + + Anti-inflammatory [312,313] Hippophae rhamnoides L. + + Anti-inflammatory [294,295] Litchi chinensis + + Neuroprotective [303,314] Prakia roxburghii -+ Neuroprotective [304] Radix astragali…”
Section: Quercetin and Kaempferol In Common Herbsmentioning
confidence: 99%
“…Fruits' intervention did not inhibit the ratio of Firmicutes to Bacteroidetes but reduced the relative abundance of Erysipelotrichaceae, which might be responsible for the anti-obesity effect [50]. Sea buckthorn (Hippophae rhamnoides L.) is rich in flavonoids, which has been reported to have the ability to regulate the gut microbiome by decreasing the abundance of Lactobacillaceae and increasing the abundance of Lachnospiraceae at the family level [84]. Total flavonoids from Chimonanthus nitens Oliv.…”
Section: Flavonoidsmentioning
confidence: 99%